# Solve Graphically (4p+8)/24-(2p-9)/6-(p+3)/18=0 4p+824-2p-96-p+318=0
Simplify each term.
Cancel the common factor of 4p+8 and 24.
Factor 4 out of 4p.
4(p)+824-2p-96-p+318=0
Factor 4 out of 8.
4p+4⋅224-2p-96-p+318=0
Factor 4 out of 4p+4⋅2.
4(p+2)24-2p-96-p+318=0
Cancel the common factors.
Factor 4 out of 24.
4(p+2)4(6)-2p-96-p+318=0
Cancel the common factor.
4(p+2)4⋅6-2p-96-p+318=0
Rewrite the expression.
p+26-2p-96-p+318=0
p+26-2p-96-p+318=0
p+26-2p-96-p+318=0
Split the fraction into multiple fractions.
p+26-(2p6-96)-p+318=0
Reduce the expression 2p6 by cancelling the common factors.
Factor 2 out of 2p.
p+26-(2(p)6-96)-p+318=0
Factor 2 out of 6.
p+26-(2p2⋅3-96)-p+318=0
Cancel the common factor.
p+26-(2p2⋅3-96)-p+318=0
Rewrite the expression.
p+26-(p3-96)-p+318=0
p+26-(p3-96)-p+318=0
Reduce the expression 96 by cancelling the common factors.
Factor 3 out of 9.
p+26-(p3-3(3)6)-p+318=0
Factor 3 out of 6.
p+26-(p3-3⋅33⋅2)-p+318=0
Cancel the common factor.
p+26-(p3-3⋅33⋅2)-p+318=0
Rewrite the expression.
p+26-(p3-32)-p+318=0
p+26-(p3-32)-p+318=0
Apply the distributive property.
p+26-p3–32-p+318=0
Multiply –32.
Multiply -1 by -1.
p+26-p3+1(32)-p+318=0
Multiply 32 by 1.
p+26-p3+32-p+318=0
p+26-p3+32-p+318=0
p+26-p3+32-p+318=0
Graph each side of the equation. The solution is the x-value of the point of intersection.
p=152
Solve Graphically (4p+8)/24-(2p-9)/6-(p+3)/18=0   ## Download our App from the store

### Create a High Performed UI/UX Design from a Silicon Valley.  Scroll to top